(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: formation processes play a crucial role in the development and expansion of lexical items within a language. This article explores the various mechanisms of word formation, including affixation, compounding, conversion, and blending, and examines their significance in the process of lexical naming.